PENGARUH KEDISIPLINAN KERJA DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA PT INSANI MEDICAL CENTRE JAKARTA - Wulandari, Fitri; Galuh Ratnagung, Catur (Journal of Research and Publication Innovation, 2024)
This research was made to determine the effect of Work Discipline and Teamwork on Employee Performance at PT Insani Medical Centre Jakarta. In this study, the method used is a quantitative method with an associative approach. The sampling technique used saturated sampling and obtained a sample of 65 respondents. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are work discipline has a significant effect on employee performance with a coefficient of determination of 90% and hypothesis testing obtained t count> t table or (22.502> 1.669). Teamwork has a significant effect on employee performance with a coefficient of determination of 93% and hypothesis testing obtained t count> t table or (28,161> 1,669). Work discipline and Teamwork simultaneously have a significant effect on employee performance with the regression equation Y = 2,149 + 0.272 X1 + 0.682 X2. The coefficient of determination is 93.1% while the remaining 6.9% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (432.559> 2.753)